Light‐induced fermenter production of derivatives of the sweet protein monellin is maximized in prestationary Saccharomyces cerevisiae cultures. Issue 8 (6th May 2022) - Gramazio, Simona; Trauth, Jonathan; Bezold, Filipp; Essen, Lars‐Oliver; Taxis, Christof; Spadaccini, Roberta
Abstract: Optogenetics has great potential for biotechnology and metabolic engineering due to the cost‐effective control of cellular activities. The usage of optogenetics techniques for the biosynthesis of bioactive molecules ensures reduced costs and enhanced regulatory possibilities. This requires development of efficient methods for light‐delivery during a production process in a fermenter. Here, we benchmarked the fermenter production of a low‐caloric sweetener in Saccharomyces cerevisiae with optogenetic tools against the production in small scale cell culture flasks. An expression system based on the light‐controlled interaction between Cry2 and Cib1 was used for sweet‐protein production. Optimization of the fermenter process was achieved by increasing the light‐flux during the production phase to circumvent shading by yeast cells at high densities. Maximal amounts of the sweet‐protein were produced in a pre‐stationary growth phase, whereas at later stages, a decay in protein abundance was observable. Our investigation showcases the upscaling of an optogenetic production process from small flasks to a bioreactor. Optogenetic‐controlled production in a fermenter is highly cost‐effective due to the cheap inducer and therefore a viable alternative to chemicals for a process that requires an induction step. Graphical Abstract and Lay Summary: Optogenetics has great potential for biotechnology and metabolic engineering due to the cost‐effective control of cellular activities. In this paper the authors benchmarked the fermenter production of a low‐caloric sweetener in Saccharomyces cerevisiae with optogenetic tools against the production in small scale cell culture flasks. The paper results show that optogenetic regulation strategies might be used efficiently in biotechnology applications.